On two new species of Halopteris Allman, 1877 (Cnidaria: Hydrozoa) from Chile - Galea, Horia R. (Zootaxa, 2006)
Two new species of hydroids, Halopteris enersis sp.nov. and Halopteris schucherti sp.nov., from the Pacific coast of southern Chile are described and figured. Measurements and nematocyst data are provided for each species. Their morphological features are compared with those of other members of the genus, and comparative tables listing their peculiarities are presented.